Epileptic manifestations in stroke patients treated with intravenous alteplase. (18th April 2017) - Bentes, C.; Martins, H.; Peralta, A. R.; Morgado, C.; Casimiro, C.; Franco, A. C.; Fonseca, A. C.; Geraldes, R.; Canhão, P.; Pinho e Melo, T.; Paiva, T.; Ferro, J. M.
Abstract : Background and purpose: Intravenous alteplase (rtPA) may be associated with seizures and epileptic activity in the electroencephalogram (EEG). The aim of this work was to compare the frequency of seizures and EEG abnormalities between stroke patients treated and not treated with rtPA. Methods: This was a prospective study of consecutive acute anterior circulation ischaemic stroke patients, with 1‐year follow‐up. Patients were previously independent, had an admission National Institute of Health Stroke Scale score ≥4, an acute ischaemic lesion and no previous seizures. They received standardized diagnostic and medical care. A video‐EEG was performed in 72 h (first EEG); during admission (daily until day 7 and after that if neurological worsening); at discharge and 1 year after stroke. Results: In all, 151 patients (101 treated with rtPA) were included. The frequency of acute and remote symptomatic seizures was not significantly different between rtPA treated and non‐treated patients ( P = 0.726 and P = 0.748, respectively). Clinical paroxysmal phenomena during rtPA perfusion were observed in five (5%) patients. In the first EEG, rtPA treated patients more often had background diffuse slowing (43.6% vs. 26.0%, P = 0.036). This difference was no longer observed at discharge (24.0% vs. 19.1%, P = 0.517) nor 1 year after (11.8% vs. 10.0%, P = 0.765). No differences were found in the frequency of epileptiform ( P = 0.867) or periodic discharges ( P = 0.381). Conclusions: Intravenous alteplase is not associated with an increased risk of clinical or electroencephalographic epileptic phenomena. Abstract : Clickhere for the corresponding questions to this CME article.